The Beliefs And Practices: Teyl Microteaching At Elementary School In Indonesia - Anita Triastuti, Dinar Martia Azizah, Sugirin, (Opción, 2019)
The research aimed to determine the beliefs, practices, and constraints faced by pre-service teachers in Teaching English for Young Learners (TEYL) microteaching. By applying qualitative method, the research was using several instruments such as interview, questionnaire, and literature review. The results show that what pre-service teachers practice during microteaching is consistent with what they believe when it comes to the ideal TEYL concept. In conclusion, simultaneous development of the four language skills within the limited time frame is problematic for the PST (Pacific Standard Time)s.